2019
DOI: 10.1097/md.0000000000013812
|View full text |Cite
|
Sign up to set email alerts
|

Effect of parecoxib in the treatment of postoperative cognitive dysfunction

Abstract: Background:Parecoxib is a selective cyclooxygenase (COX)-2 inhibitor widely used as an analgesia technique in perioperative period for its potent anti-inflammatory and analgesic effects. However, litter is known about its effect on postoperative cognitive dysfunction (POCD). The purpose of this meta-analysis of randomized controlled trials (RCTs) was to evaluate the effect of parecoxib in the treatment of postoperative cognitive dysfunction.Methods:We searched PubMed, Cochrane Library and Embase databases for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 34 publications
(39 reference statements)
1
16
0
2
Order By: Relevance
“…Perioperative neurocognitive disorder (PND) is a common cognitive complication of surgery, especially among older patients, which is characterized by progressive cognitive deterioration in the preoperative or postoperative period. PND has several clinical manifestations, including attention deficits, learning disabilities and memory loss (1,2). In the long term, PND can result in prolonged hospitalization, decreased quality of life and increased financial burden on the family and society (3).…”
Section: Introductionmentioning
confidence: 99%
“…Perioperative neurocognitive disorder (PND) is a common cognitive complication of surgery, especially among older patients, which is characterized by progressive cognitive deterioration in the preoperative or postoperative period. PND has several clinical manifestations, including attention deficits, learning disabilities and memory loss (1,2). In the long term, PND can result in prolonged hospitalization, decreased quality of life and increased financial burden on the family and society (3).…”
Section: Introductionmentioning
confidence: 99%
“…POCD can prolong hospital course, hinder disease recovery, raise postoperative complications and lower the quality of life after discharge . Yet, the current approaches to prevention and treatment for POCD are quite rare, and the treatment effect is still unsatisfactory . Therefore, it is important to find more effective approaches to treat POCD.…”
mentioning
confidence: 99%
“…In clinical practice, S-100β protein and IL-6 can be used as biological and chemical markers of postoperative cognitive dysfunction to evaluate brain injury. 24,25 The S-100 protein family belongs to a group of acidic proteins that can connect with calcium and affect various cellular responses in the calcium signalling transduction pathway. 26 S-100β is an important member of the S-100 family.…”
Section: Discussionmentioning
confidence: 99%
“…24 A plenty of studies found that S-100β protein and IL-6 levels are positively associated with POCD. 24,25 Melatonin (N-acetyl-5-methoxytryptamine) is an endogenous hormone produced by the pineal gland and released exclusively at night. 29 Cortisol is one of the major glucocorticoid hormones secreted by the adrenal cortex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation